Analysis of Differences in Quality of Work Life and Work Motivation on Job Satisfaction Between Married and Unmarried Employess - Eggie Nuravita Denny; Bambang Moertono; Marwan Marwan (Dinasti Publisher, 2024)
The study aimed to find out the differences in quality of work life and work motivation on job satisafaction between married and unmarried employees. This study used quantitative research methods, with data collection techniques through questionnaires and literature study. The number of samples were 101 respondents who were employees of various companies and institution, located in Yogyakarta with the majority from educational institutions. The descriptive statistics were used to test the research instrument. The instrument test used the validity and reliability test, the classical assumption test (normality, multicollinearity, heteroscedasticity, and linearity), hypothesis testing (f test, t-test, and independent sample t-test), multiple linear regression analysis, and the coefficient of determination (R2). The results of this study indicate that: 1) the quality of work life has an effect on the dependent variable of job satisfaction. 2) work motivation has an effect on the dependent variable of job satisfaction. 3) the quality of work life and work motivation simultaneously have a positive and significant effect on the dependent variable of job satisfaction. 4) the quality of work life of married employees and unmarried employees is not the same (significantly different). 5) the work motivation of married employees and unmarried employees is the same (not significantly different). 6) the job satisfaction of married employees and unmarried employees is not the same (significantly different).